PENGARUH GAYA KEPEMIMPINAN TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. TELKOM CABANG BIMA - Ramlin Ramlin; Wulandari Wulandari (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract This study aims to determine the effect of leadership style on employee morale at PT Telkom Branch Bima. The number of samples of 53 people was obtained and is a population study because it uses the entire population to be the sample. with a saturated sample technique (total population). The instrument in this study was a questionnaire with a Likert scale. Testing instruments using validity and reliability tests. Methods of data analysis using simple linear regression with correlation coefficient test, coefficient of determination and t test. The results showed that the leadership style variable (X) had a significant effect on employee morale at PT. Telkom Branch Bima. From the t-test calculation, the t-count value is greater than the t-table value (4.622> 2.007) with a significant level smaller than 0.05 (0.000 <0.05). In addition, the R Square value of 0.543 (54.3%) indicates that leadership style has a strong enough relationship with employee morale at PT. Telkom Branch Bima.